Antibacterial Activities of Lichen Derived Extracts against Different Bacillus Species from Soak Liquor Samples - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2020)
In the leather industry, some bacterial strains may become resistant to antibacterial agents utilized in the soaking process due to long-term use and/or not using in sufficient doses. Alternative approaches or novel agents need to be investigated to overcome antibacterial resistance of bacteria present in the soaking process. These alternative approaches may be from natural resources such as lichens which are known to have various biological activities such as antibacterial, antifungal etc. For this purpose, soak liquor samples from different tanneries were collected and eight isolates from these samples were identified by cultural and molecular techniques. Also, the antibacterial effects of acetone extracts of Hypogymnia physodes, Evernia divaricata, Pseudevernia furfuracea and Usnea sp. at different concentrations were tested on these isolates. They were all Gram (+), rod shaped, oxidase (+), catalase (+), protease (+). Six isolates had lipase activities. The isolates were assigned to Bacillus toyonensis, B. mojavensis, B. subtilis, B. amyloliquefaciens, B. velezensis, B. cereus, and B. licheniformis in molecular analyses. The acetone extracts of Evernia divaricata totally killed B. toyonensis, B. mojavensis, B. amyloliquefaciens, and B. subtilis at the concentrations of 240, 120, 60 and 30 mu g/ml, respectively. These extracts had also significant antibacterial efficacies on B. cereus, B. velezensis, B. licheniformis at the concentration of 240 mu g/ml. The acetone extracts of P. furfuracea had a great inhibitory effect on the growth of most species (80.24-88.65%) only at the concentration of 240 mu g/ml. H. physodes acetone extracts totally killed B. amyloliquefaciens and had considerably high suppressive effect on the growth of other tested bacteria at the concentrations of 120 and 240 mu g/ml. Usnea sp. acetone extracts had inhibitory effect on Bacillus species (86.697.9%) even at the 30 mu g/ml concentration. In this respect, lichens may provide an alternative approach for the leather industry to overcome bacterial resistance to the antibacterial agents.
Keywords: MODERATELY HALOPHILIC BACTERIA; ANTIMICROBIAL ACTIVITY; LEATHER; HIDE; IDENTIFICATION; PRESERVATION; QUALITY; SKINS